Dual-corona Comptonization model for the type-b quasi-periodic oscillations in GX 339-4 - Peirano, Valentina (2023)
Characterizing the fast variability in black hole low-mass X-ray binaries (BHXBs) can help us to understand the geometrical and physical nature of the innermost regions of these sources. Particularly, type-B quasi-periodic oscillations (QPOs), observed in BHXBs during the soft-intermediate state (SIMS) of an outburst, are believed to be connected to the ejection of a relativistic jet. The X-ray spectrum of a source in the SIMS is characterized by a dominant soft blackbody-like component - associated with theVaccretion disc - and a hard component - associated with a Comptonizing region or corona. Strong type-B QPOs were observed by NICER and AstroSat in GX 339-4 during its 2021 outburst. We find that the fractional rms spectrum of the QPO remains constant at ~1 per cent for energies below ~1.8 keV, and then increases with increasing energy up to ~17 per cent at 20-30 keV. We also find that the lag spectrum is 'U-shaped', decreasing from ~1.2 rad at 0.7 keV to 0 rad at ~3.5 keV, and increasing again at higher energies up to ~0.6 rad at 20-30 keV. Using a recently developed time-dependent Comptonization model, we fit simultaneously the fractional rms and lag spectra of the QPO, and the time-averaged energy spectrum of GX 339-4 to constrain the physical parameters of the region responsible for the variability we observe. We suggest that the radiative properties of the type-B QPOs observed in GX 339-4 can be explained by two physically-connected comptonizing regions that interact with the accretion disc via a feedback loop of X-ray photons.